LIABILITY OF THE REPUBLIC OF CROATIA FOR ANY DAMAGE SUFFERED THROUGH COMPROMISING THE REAL PROPERTY REGISTRATION AND CADASTRE JOINT INFORMATION SYSTEM - Pichler, Davorin (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Until their digitation, land registries in the Republic of Croatia had been kept manually (paper-based registration). The Land Registry Act stipulates that land registries in the Republic of Croatia are kept electronically by means of a Real Property Registration and Cadastre Joint Information System (hereinafter: JIS) containing harmonized real property and cadastral data. A real property and land database is created through the electronic entry of paper-based data. i.e. integration of real property and cadastral data into a single database. Hence, the protection of real property transfers is enhanced since the legal status of the land and all accompanying restrictions (concessions, public property status etc.) can be obtained in one place. The real property land database enables registration of every change to the real property without the need to inform both the land registration court and cadastre thereabout. The Real Property Registration and Cadastre Joint Information System is jointly coordinated and managed by the Ministry of Justice and Administration of the Republic of Croatia and the State Geodetic Administration. The Land Registry Act sets forth that the Republic of Croatia is strictly liable for any damage arising from flaws in keeping land registries. Such damage can occur if it comes to errors or malfunctions in the respective joint information system. This paper investigates the appropriateness of the measures for protection of the Real Property Registration and Cadastre Joint Information System and the general rules for security and control of the access to the said system, and analyse the risk of compromising it. Regarding the liability of the Republic of Croatia for any damage pertaining to flaws in the land records management, the paper depicts the model of defining the liability for any damage suffered by the holders of ownership rights due to unauthorized access to the said joint information system. The paper also sheds light on the advantages and disadvantages of the model for defining fault and strict liability in the above case and examines some pending issues relating to the applicable model for defining such damage liability de lege lata as well as possible legal solutions and the potential need for intervention by the legislator de lege ferenda.
Keywords: damage; land registry; cadastre; information system; digitization